2014
DOI: 10.1177/0271121414536784
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Emergent-Literacy Skills and Home-Literacy Environment of Children With Autism and Their Peers

Abstract: The purpose of the current study was to characterize and compare the emergent-literacy skills, print interest, and home-literacy environment of children with autism spectrum disorder (ASD) to their peers, as well as to examine the association between children’s emergent-literacy skills and their home-literacy environment. Results indicated that children with ASD had significantly higher alphabet knowledge and significantly lower print-concept knowledge when controlling for language ability compared with their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
84
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(92 citation statements)
references
References 42 publications
8
84
0
Order By: Relevance
“…The results of this study also support the findings of other studies of preschool children with ASD that the pattern found in older readers with ASD of relative strength in word reading and weakness in reading comprehension (e.g., Brown et al, 2013; Nation et al, 2006) appears to be established early (Davidson & Weismer, 2014; Dynia et al, 2014; Dynia et al, 2017; Lanter et al, 2012). In the young children, it is print-related skills that are stronger and listening comprehension and vocabulary that are weaker, but the pattern appears to be similar.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of this study also support the findings of other studies of preschool children with ASD that the pattern found in older readers with ASD of relative strength in word reading and weakness in reading comprehension (e.g., Brown et al, 2013; Nation et al, 2006) appears to be established early (Davidson & Weismer, 2014; Dynia et al, 2014; Dynia et al, 2017; Lanter et al, 2012). In the young children, it is print-related skills that are stronger and listening comprehension and vocabulary that are weaker, but the pattern appears to be similar.…”
Section: Discussionsupporting
confidence: 90%
“…Wide-spread difficulties with reading comprehension, often associated with average or better word reading accuracy, have been reported (Brown et al, 2013; Nation et al, 2006; O’Connor & Klein, 2004; Rickets, Jones, Happe, & Charman, 2013). An emerging body of research demonstrates that preschoolers with ASD show a pattern similar to that found in older readers with ASD: great heterogeneity, relatively stronger knowledge of print-related skills and relatively weaker oral language and phonological awareness skills (Davidson & Weismer, 2014; Dynia, Lawton, Logan, & Justice, 2014;Dynia, Brock, Justice, & Kaderavek, 2017; Lanter, Watson, Erickson, & Freeman, 2012; Westerveld et al, 2015) although Dynia et al (2014) found that the difference in phonological awareness disappeared when they controlled for oral language. As well, Dynia et al (2017) found that among young children with ASD, phonological awareness in preschool predicted later decoding achievement in kindergarten.…”
Section: Emergent Literacy and Children With Asdmentioning
confidence: 94%
“…To date, the limited research on the HLE of children with ASD has focused on the preschool years and indicates that the majority of parents read to their child at least twice a week, which is similar to TD families (Dynia et al, ; Lanter, Freeman, & Dove, ). Likewise, the current study of school‐aged children found that 85% of children with ALD participated in shared reading activities on at least a weekly basis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the ASD group was older and had better procedural print‐related skills (such as alphabetic, phonemic and word knowledge), so they were likely better equipped to access resources independently. Dynia et al () found that children aged 3–5 with ASD requested shared reading less often than their TD peers, on average three times per week rather than five times a week. However, independent reading frequency did not differ, with both groups of children reading on their own five times a week on average.…”
Section: Home Literacy Environments Of Children With Autism Spectrummentioning
confidence: 99%
See 1 more Smart Citation